Storability and Chips Quality of Chemical Treated Potatoes under Ordinary Condition - Ishwori P. Gautam; Moha D. Sharma; Bhim B. Khatri; Resham B. Thapa; Kanti Shrestha (Journal of Basic & Applied Sciences, 2013)
Storage experiments were conducted under ordinary room conditions in the mid hill, Khumaltar (1350 masl ; meter above sea level) and high hills, Daman (2200 masl) of Nepal during the summer season of 2011 to find out the effect of chemical treatments and their time of applications on storability and chips qualities of potato cv. Kufri Jyoti. Chemicals treatments were; CIPC (Isopropyl N (3 chlorophenyl) carbamate), hydrogen peroxide and calcium chloride, which were applied as a single dose (before storage) and double dose (before and at 45 days in storage). Ordinary water treated potatoes served as control. The treatments were replicated thrice. Apparently healthy tubers > 60 gram weight after different chemical treatments were stored in bamboo racks and wooden tray, respectively at Kumaltar and Daman for 120 days. Observations were recorded on weight loss percentage (WLP), sprouting percentage, numbers and weight of sprouts and quality parameters for chips. Double fumigation with CIPC was effective for inhibition of sprouting and reduction of postharvest loss up to 120 days in both the locations. On the other hand the better colour of the chips was produced by two times hydrogen peroxide treated potatoes.